Penerapan Metode Pembelajaran Kooperatif Berbasis Kasus Terhadap Efektivitas Pembelajaran Mahasiswa Akuntansi Universitas Kristen Maranatha - Aurora Angela; Lauw Tjun Tjun; Sunardi Indrawan; Ray Krismawan (Universitas Kristen Maranatha, 2017)
AbstractÂ The quality of learning is not only limited to the effectiveness of knowledge transfer, but also on the development of basic attitudes, such as critical scientific academic attitudes and continual willingness to seek the truth. In this case, educators are required not only to transfer of knowledge, but more than that also acts as an enlightenment agent. Therefore, this study aims to obtain empirical evidence of the influence of application of case-based cooperative learning methods to the learning effectiveness of the accounting students on Maranatha Christian University.The technique used to test the hypothesis is Simple Linear Regression Analysis, which used to know the influence of the application of case-based cooperative learning method to the effectiveness of student learning. Respondents in this study are accounting students of Maranatha Christian University.The result of this study shows that case-based cooperative learning method positively affects the learning effectiveness of the accounting students on Maranatha Christian University.Â Keywords: Case-Based Cooperative Learning Method, Learning Effectiveness.